2020
DOI: 10.1063/1.5141102
|View full text |Cite
|
Sign up to set email alerts
|

Helical-chiroptical nanowires generated orbital angular momentum for the detection of circularly polarized light

Abstract: In this work, we designed a type of organic chiral polymeric nanowire with strong orbital angular momentum to fabricate circularly polarized light detectors. In chiral polymeric nanowires, chirality induced orbital angular momentum could lead to the splitting of spin up and spin down energy levels, which determines the performance of circularly polarized light detection. In addition, chiral polymeric nanowire based circularly polarized light detectors exhibit excellent reversibility and stability after several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…In contrast, the 1D chain extends to the carrier transporting direction in the device, resulting in the higher photoconductivity than 2D structure. In addition, the high photoconductivity in the helical 1D structure under CPL irradiation probably depends on the direction of the polarized electronic spin generated by selective absorption of CPL with angular momentum ( 17 , 28 ). These effects have been reported in chiral perovskites with strong spin-orbit coupling, which can be explained by spin-dependent optical selection rules and large Rashba splitting ( 29 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the 1D chain extends to the carrier transporting direction in the device, resulting in the higher photoconductivity than 2D structure. In addition, the high photoconductivity in the helical 1D structure under CPL irradiation probably depends on the direction of the polarized electronic spin generated by selective absorption of CPL with angular momentum ( 17 , 28 ). These effects have been reported in chiral perovskites with strong spin-orbit coupling, which can be explained by spin-dependent optical selection rules and large Rashba splitting ( 29 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further, an anisotropy factor of photocurrent for the self‐powered photodetection of CPL is acquired to be 0.3, which reaches the unprecedented merit for the chiral hybrid perovskites. The high anisotropy factor is probably attributable to the polarized electronic spin induced by orbital angular momentum [14] . Spin orbit coupling and resulting spin splitting are expected in the compound constituted of heavy elements Bi and I, which may lead to large Rashba splitting in chiral structure lacking of inversion symmetry [15] .…”
Section: Figurementioning
confidence: 99%
“…The high anisotropy factor is probably attributable to the polarized electronic spin induced by orbital angular momentum. [14] Spin orbit coupling and resulting spin splitting are expected in the compound constituted of heavy elements Bi and I, which may lead to large Rashba splitting in chiral structure lacking of inversion symmetry. [15] To our best knowledge, it should be the first lead-free halide double perovskite for self-powered CPL detection and will enlighten the development of new "green" CPL detectors with prominent performance.…”
mentioning
confidence: 99%
“…Moreover, the detectivity value (D*) of the CPL detector based on chiral polythiophene exceeded 1.6 × 10 10 Jones ranging from 400 to 670 nm ( Figure 10C ), and it reached 1.25 × 10 11 Jones at 553 nm. Most importantly, the experimental results showed that the differential absorption between LCPL and RCPL had a small contribution to the detection of CPL, while chirality-induced OAM played an important role in the CPL detection for achiral PT nanowire–based CPL photodetectors ( Wang et al, 2020 ). This study plays a very important role in understanding the detection mechanism of CPL photodetectors.…”
Section: Circularly Polarized Light Photodetector Mechanismmentioning
confidence: 99%
“… (A) TEM and scheme of the chiral PT nanowire structure, (B) schematic diagram of the setup used for CPL detection, (C) wavelength-dependent detectivity ( D* ) of the chiral PT–based photodetectors, and (D) photocurrent of ITO/ZnO/chiral PT:PCBM/MoO 3 /Ag under the stimuli of left-handed and right-handed CPL illumination ( Wang et al, 2020 ). Reproduced with permission.…”
Section: Circularly Polarized Light Photodetector Mechanismmentioning
confidence: 99%